2022
DOI: 10.1001/jamaneurol.2022.1858
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Benzodiazepines or Antihistamines for Patients With Acute Vertigo

Abstract: IMPORTANCE Acute vertigo can be disabling. Antihistamines and benzodiazepines are frequently prescribed as "vestibular suppressants," but their efficacy is unclear.OBJECTIVE To assess the efficacy of antihistamines and benzodiazepines in the treatment of acute vertigo from any underlying cause.DATA SOURCES We searched the PubMed, CENTRAL, EMBASE, CINAHL, Scopus, and ClinicalTrials.gov databases from inception to January 14, 2019, without language restrictions. Bibliographies of the included studies and relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Valid approaches have already been examined and include change of medication as well as nonpharmacological treatment, such as physical exercises or behavioral therapy (Holt et al, 2010). The use of AS medication in symptomatic therapy of VDB remains debated (Hunter et al, 2022). Our results support recent recommendations that their use as vestibular suppressants should be limited only to the acute phase of the disease and must be used with special caution in the older population (Casani et al, 2021).…”
Section: Impact Of As Medication On Generic and Vertigo-specific Func...supporting
confidence: 69%
“…Valid approaches have already been examined and include change of medication as well as nonpharmacological treatment, such as physical exercises or behavioral therapy (Holt et al, 2010). The use of AS medication in symptomatic therapy of VDB remains debated (Hunter et al, 2022). Our results support recent recommendations that their use as vestibular suppressants should be limited only to the acute phase of the disease and must be used with special caution in the older population (Casani et al, 2021).…”
Section: Impact Of As Medication On Generic and Vertigo-specific Func...supporting
confidence: 69%
“…There was no evidence to suggest that antihistamines increased the likelihood of complete symptom remission after one week and one month (relative risk, RR = 1.03, 95% CI 0.56–1.89). Authors found fairly persuasive evidence that single-dose antihistamines were superior to benzodiazepines in relieving vertigo symptoms after 2 h. Furthermore, the evidence did not support an association between benzodiazepine use with an improvement in any symptom of acute vertigo at all [ 17 ].…”
Section: New Findingsmentioning
confidence: 99%
“…
This issue of JAMA Neurology includes a methodologically rigorous systematic review and meta-analysis examining the efficacy of benzodiazepines and antihistamines in patients with acute vertigo. 1 Hunter and colleagues 1 chose an important, common clinical problem, systematically searched for relevant evidence, and then assessed the studies for both quality and risk of bias. Their primary outcome was symptom control of vertigo at 2 hours measured by a visual analog score.
…”
mentioning
confidence: 99%
“…Hunter and colleagues found that antihistamines were superior to benzodiazepines at 2 hours but not at 1 week or 1 month. Importantly, as the authors themselves acknowledge, we do not know if the statistically significant difference in self-rated symptom severity is clinically meaningful.…”
mentioning
confidence: 99%
See 1 more Smart Citation